THE CHANGING FACE OF HR FUNCTION: FROM ADMIN TO A BUSINESS PARTNER - Bhawana Pande, Ashutosh Priya, Prof. Tulika Saxena, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Management of human resource is a pivotal part of every organization. It is basically linked to employees who are working in the organization and as well as with the relationships between them and outside the organization. In the recent years, HRM has gone through various transformations in its role from being a manpower supporter to a business partner in maintaining a competitive edge of the enterprise. During industrial revolution, the personnel management which was limited to employee wages and record keeping, then reformed its aspect and evolved as Human resource management which had key concerns for recruiting skilled labourforce, training and developing workforce and performance management. With due course of time, HR underwent a sizable shift approximately 15 years in the past right into a business partner model that might the businesses to attach HR facilities of excellence to the unique needs of the business. While administration and worker advocacy persevered to be critical, HR was rising as a critical strategic associate and catalyst for the business. This paper mainly emphases on changing role of the functions of human resource management in response to the various pressures that arise because of the uncertainty in the environment. Additionally, it also addresses the various challenges& pressures that lie in front of HR because of the change in the environment.The study has been done through analysis of literature review and the nature of research methodology is qualitative in nature.